Development and In Vivo Evaluation of pH-Responsive Chitosan/Alginate Hydrogel-Based Films Co-Loaded With Carissa Carandas L. Anthocyanins and Gallic acid for Wound Healing and Monitoring - Thanh Phuong Nguyen; Phuong T.M. Ha; Duc Khanh Linh Le; Hong Phuong Thao Tieu; Ngoc Yen Nguyen; Gia Khuong Huynh; Phat Dat Trinh; Thanh Phuoc Le; Duy Toan Pham (Journal of Pharmaceutical Innovation, 2026)

Trace Metal Concentrations in Rainwater, Sources, and Health Risks: A Case Study of Hanoi, Vietnam - Thi Phuong Quynh Le; Nhu Da Le; Thi Thu Ha Hoang; Thi Mai Huong Nguyen; Thi Xuan Binh Phung; Emma Rochelle-Newall; Thi Anh Huong Nguyen; Thi Ngoc Mai Pham; Thi Minh Hanh Pham; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen (International Journal of Environmental Research, 2026)

Tailoring the morphology and surface plasmon coupling of BiVO4 toward efficient visible-light degradation of antibiotic pollutants - Thinh B. Le; Van M. Dinh; Phuong T.M. Ha; Dat H. Nguyen; Thien P. Nguyen; Nhi T. Y Nguyen; Tuan A. Nguyen; YB.N. Tran; Kim-Ngan N. Phan; Hiep Q. Ha; Dai-Viet N. Vo (Environmental Research, 2026)

Nickel/activated biochar catalysts from agricultural waste for transforming carbon dioxide into renewable natural gas - Ba Long Do; Thi Thanh Binh Mai; Thi Bich Ngan Nguyen; Thanh Gia-Thien Ho; Phuoc Dat Duong; Thi Quynh Nhu Ngo; Phuc Hoang Duy Nguyen; Thi Thuy Phuong Pham; Ky Phuong Ha Huynh; Thi Thuy Van Nguyen; Tri Nguyen (Biomass and Bioenergy, 2026)

A methodological assessment and reflection on member checking as a form of participant validation for conservation social science - Judith J. Rakowski; Trong Dat Cao Tien; Trung Cao Tien; Ha Trang Nguyen; Juan Martin Dabezies; Laure Joanny; Meredith L. Gore (Conservation Biology, 2026)
Qualitative approaches are increasingly applied in conservation social science, yet methodological reflection remains limited. Member checking, a process of returning findings to participants for feedback, is widely recognized outside conservation as a means to enhance rigor and reciprocity, but it is rarely reported in conservation research. This paper assesses and reflects on the implementation of member checking within a participatory study on conservation crime prevention in Pù Mát National Park, Vietnam. The member checking process involved 18 sessions with 88 participants representing community members, park staff, nongovernmental organizations, and university researchers. Member checking was used to revisit and refine preliminary interpretations of data collected during previous fieldwork phases. Findings indicated that the process strengthened credibility, confirmability, dependability, and transferability of results while fostering transparency, accountability, and mutual learning. Challenges related to linguistic diversity, power asymmetries, and logistical constraints revealed limits to its universality as a validation tool. The greatest value of member checking for conservation social science lies not in confirming truth but in fostering iterative dialogue, reflexivity, and shared understanding. Approached as a form of participatory reflection, member checking can help bridge methodological rigor and ethical practice, contributing to more equitable and context‐sensitive conservation social science research. We offer practical recommendations for integrating member checking into conservation projects and helping translate principles of reflexive and participatory research into conservation practice.

Integrated eDNA and conventional surveys of coral reef fishes at submerged banks, shoals, and offshore Islands in Southern Vietnam - Long Van Nguyen; Quang Minh Thai; Dat Xuan Mai; Thinh Cong Tran; My Thao Nguyen-Le; Hong Kim Thi Phan; Ben Xuan Hoang; Ha Viet Dao; Binh Thuy Dang; Oanh Thi Truong; Sang Quang Tran (Regional Studies in Marine Science, 2026)

A new 14-membered cembrane-type diterpenoid and other constituents from the aerial parts of Jatropha integerrima Jacq. and their antibacterial activity - Hanh Nhu Thi Hoang; Ton That Huu Dat; Le Canh VietCuong; Hung Quoc Vo; Linh Thuy Khanh Nguyen; Le Thanh Long; Le Thu Ha; Bao Chi Nguyen; Hoai Thi Nguyen; Duc Viet Ho (Natural Product Research, 2026)

When coping means breaking the rules: Understanding conservation crime through strain - Judith J. Rakowski; Michelle Anagnostou; Trong Dat Cao Tien; Trung Cao Tien; Laure Joanny; Ha Trang Nguyen; James L. Slade; Luan Van Nguyen; Elle Jingjing Xu; Meredith L. Gore (Biological Conservation, 2026)

Phenolic glycosides from Ligusticum wallichii with cytotoxic activity - Ninh Khac Thanh Tung; Nguyen Thi Tu Oanh; Nguyen Thi Minh Hang; Nguyen Thi Thu Ha; Tran My Linh; Vu Huong Giang; Yohan Seo; SeonJu Park; Nguyen Tien Dat; Nguyen Xuan Nhiem; Hyung Min Kim; Ninh Khac Ban (Phytochemistry Letters, 2026)

Synthesis, characterization, and ethanol vapor sensing characteristics of vanadium-based-MOFs with and without Cu doping - Tan Le Hoang Doan; Tae-Un Kim; Yujin Kim; My Van Nguyen; Ali Mirzaei; Ngoc Xuan Dat Mai; Linh Ho Thuy Nguyen; Hanh-Vy Tran Nguyen; Ha-Van Nguyen; Nhat Minh Quang Tran; Thang Bach Phan; Hyoun Woo Kim; et al. (Chemical Engineering Journal, 2026)

New prunasin derivatives, bachmasides A and B, with α-glucosidase inhibitory activity from the leaves of Elaeocarpus bachmaensis - Phan Thi Diem Tran; Vu Thi Thanh Tam; Tran Phuong Ha; Le Tuan Anh; Le Trung Hieu; Ton That Huu Dat; Le Canh Viet Cuong (Journal of Natural Medicines, 2026)

A new species, Rugonectria artocarpicola sp. nov., causing canker disease of jackfruit in Vietnam - Tran Ngoc Khanh; Do Xuan Dat; Vu Thi Phuong Binh; Ha Minh Thanh; Lai Tien Dung; Le Dinh Thao (Mycological Progress, 2025)

Retraction notice to ‘Construction of S-scheme CdS/g-C3N4 nanocomposite with improved visible-light photocatalytic degradation of methylene blue’ [Environ. Res. 206 (2022) 112556] - Kim Nguyen Van; Ha Tran Huu; Viet Nga Nguyen Thi; Thanh-Lieu Thi Le; Quoc Dat Hoang; Quoc Viet Dinh; Vien Vo; Dai Lam Tran; Yasser Vasseghian (Environmental Research, 2025)

Rapid fabrication of expanded vermiculite with microwave as low-cost adsorbent for removal of arsenic from water - Thu Ha Dao; Duong Duc La; Van Chinh Tran; Manh Ha Nguyen; Duy Dat Nguyen; Van Huy Nguyen; Van Huyen Luu; Thi Hoai Phuong Nguyen (International Journal of Environmental Science and Technology, 2025)

Diosgenin glycosides from Paris vietnamensis (Takht) H.Li with cytotoxic and inhibitory NO production activities - Le Tuan Anh Hoang; Van Cong Pham; Viet Duc Ngo; Van Hieu Ngo; Van Manh Nong; Ha Phuong Lai; Thanh Tuan Do; Tien Dat Nguyen; Ngoc Tung Nguyen (Natural Product Research, 2025)

Chemical constituents from symplocos sumuntia and their anti-inflammatory effect - Tran Thu Huong; Nguyen Van Thong; Tran Anh Quang; Le Huyen Tram; Le Thi Thuy; Nguyen Thi Thuy My; Nguyen Tuan Anh; Nguyen Tuan Hiep; Nguyen Ngoc Linh; Duc-Dat Le; Tran Thu Ha; Bui Van Thanh (Natural Product Research, 2025)

Lignin nano/micro-particles from agricultural biomasses: Developing direct precipitation for integrated biorefinery - Tuyen B. Ly; Dat D.B. Nguyen; Anh M.H. Trinh; Nhi T.T. Tran; Thi H.M. Truong; Kien A. Le; Ha V. Le; Phung K. Le (Bioresource Technology, 2025)

Spatial recruitment patterns of Chaetodon butterflyfishes on coral reefs in the coastal waters of Vietnam - Long Van Nguyen; Quang Minh Thai; Dat Xuan Mai; My Thao Nguyen-Le; Hong Kim Thi Phan; Ben Xuan Hoang; Ha Viet Dao; Marina Malyutina (Environmental Biology of Fishes, 2025)

Lycopodiaceae herb from Vietnam as a promising medicinal source of natural hupezine and novel huperzine-producing endophytic fungi - Thanh Thi Minh Le; Ha Thi Thu Trinh; Ha Thanh Pham; Dat Tien Nguyen; Giang Hoang Do; Hien Thuy Phan; Tam Duc Le; Ngoc Tung Quach; Tien Quyet Phi; Ha Hoang Chu (Biotechnology Letters, 2025)

Occurrence and ecological risks of antibiotics and antiparasitics in surface water in urban lakes in Hanoi city, Vietnam - Nhu Da Le; Thi Thanh Huyen Dinh; Thi Huong Vu; Phuong Thu Le; Thi Mai Huong Nguyen; Thi Thu Ha Hoang; Emma Rochelle-Newall; Thi Xuan Binh Phung; Thi Thuy Duong; Thi Huyen Trang Luu; Thi Lan Phuong Kieu; Thi Anh Huong Nguyen; et al. (Environmental Science and Pollution Research, 2024)

Phytochemical analysis and quality assessment of Podocarpus macrophyllus by UHPLC-DAD-ESI-MS and UHPLC-MS/MS MRM methods - Duc Dat Le; JeongJun Ahn; Sanghee Han; Seok-Geun Lee; Mina Lee; In Jin Ha (Natural Product Research, 2024)

Microbial contamination in a large drinking water reservoir in north Vietnam - Nhu Da Le; Thi Mai Huong Nguyen; Thi Thu Ha Hoang; Emma Rochelle-Newall; Thi Xuan Binh Phung; Thi Minh Hanh Pham; Thi Thuy Duong; Tien Dat Nguyen; Thi Phuong Quynh Le (Aquatic Sciences, 2024)

A new circulation in glycolysis of polyethylene terephthalate using MOF-based catalysts for environmental sustainability of plastic - Duong Dinh Pham; Dat-Nguyen Vo; Mai Thanh Phong; Huu Hieu Nguyen; Trung Nguyen-Thoi; Thuy-Phuong T. Pham; Duy Ha Le Phuong; Le Kim Hoang Pham; Da Hye Won; Dang Le Tri Nguyen; Tung M. Nguyen (Chemical Engineering Journal, 2024)

Chemical constituents from the heterotrophic marine microalgae Aurantiochytrium sp. SC145 and their antimicrobial activities - Nguyen Thi Thu Thuy; Hoang Thi Minh Hien; Nguyen Cam Ha; Le Thi Thom; Dang Diem Hong; Nguyen Van Thinh; Nguyen Trong Dan; Nguyen Dang Hoi; Vu Thi Loan; Hoang Duc Quang; Dan Thi Thuy Hang; Phan Van Kiem; et al. (Natural Product Research, 2024)

Metal contamination, their ecological risk, and relationship with other variables in surface sediments of urban rivers in a big city in Asia: case study of Hanoi, Vietnam - Thi Xuan Binh Phung; Thi Phuong Quynh Le; Nhu Da Le; Thi Thu Ha Hoang; Thi Mai Huong Nguyen; Emma Rochelle-Newall; Thi Anh Huong Nguyen; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen (Environmental Science and Pollution Research, 2024)

Total resource management model towards carbon neutrality in Vietnam construction industry: A hierarchical framework - Tat-Dat Bui; Hien Minh Ha; Thi Phuong Thuy Tran; Ming K. Lim; Anthony SF Chiu; Ming-Lang Tseng (Resources, Conservation and Recycling, 2024)

Sea-level trends and variability along the coast of Vietnam over 2002–2018: Insights from the X-TRACK/ALES altimetry dataset and coastal tide gauges - Dat T. Pham; William Llovel; Truong M. Nguyen; Huy Q. Le; Minh N. Le; Huong T. Ha (Advances in Space Research, 2024)

Metabolic and genomic analysis deciphering biocontrol potential of endophytic Streptomyces albus RC2 against crop pathogenic fungi - Ngoc Tung Quach; Thi Hanh Nguyen Vu; Thi Thu An Nguyen; Phuong Chi Le; Hoang Giang Do; Tien Dat Nguyen; Phan Thi Hong Thao; Thi Thanh Loi Nguyen; Hoang Ha Chu; Quyet-Tien Phi (Brazilian Journal of Microbiology, 2023)

Comparative performance and machine learning-based optimization of TSA configurations for NH3 removal from NH3 cracking gas - Dat-Nguyen Vo; Jae Hun Chang; Suk-Hoon Hong; Chang-Ha Lee (Chemical Engineering Journal, 2023)

Enhancing energy efficiency of chemical absorption-based CO2 capture process with advanced waste-heat recovery modules at a high capture rate - Zhiwei Zhang; Dat-Nguyen Vo; Jaesung Kum; Suk-Hoon Hong; Chang-Ha Lee (Chemical Engineering Journal, 2023)

Advances in Earth observation and machine learning for quantifying blue carbon - Tien Dat Pham; Nam Thang Ha; Neil Saintilan; Andrew Skidmore; Duong Cao Phan; Nga Nhu Le; Hung Luu Viet; Wataru Takeuchi; Daniel A. Friess (Earth-Science Reviews, 2023)

Microbial contamination in the coastal aquaculture zone of the Ba Lat river mouth, Vietnam - Nhu Da Le; Thi Thu Ha Hoang; Thi Mai Huong Nguyen; Emma Rochelle-Newall; Thi Minh Hanh Pham; Thi Xuan Binh Phung; Thi Thuy Duong; Thi Anh Huong Nguyen; Le Minh Dinh; Thanh Nghi Duong; Tien Dat Nguyen; Thi Phuong Quynh Le (Marine Pollution Bulletin, 2023)

Performance and ANN-based optimization of an advanced process for wet CO2-to-Methanol using a catalytic fluidized bed reactor integrated with separators - Vo Dat Nguyen; JaeHun Chang; Suk-Hoon Hong; Chang-Ha Lee (Fuel, 2023)

Anti-inflammatory lignan and triterpenoid compounds from the twigs of Ligustrum lucidum - Da Hye Sim; Ngoc Khanh Vu; Duc Dat Le; Ha Ryong Kim; Eun Sook Ma; Byung Sun Min; Mi Hee Woo (Phytochemistry Letters, 2023)

Microwave-assisted polyol liquefication from bamboo for bio-polyurethane foams fabrication - Tuan An Nguyen; Tuyet Minh Nguyen Ha; Binh T. Nguyen; Dat Ha; Tuan Vu Vo; Dang Mao Nguyen; Dang Khoa Vo; Ngoc Thuy Nguyen; Tuong Vy Nguyen; DongQuy Hoang (Journal of Environmental Chemical Engineering, 2023)

A new steroidal saponin from the aerial parts of Solanum torvum - Le Canh Viet Cuong; Nguyen Phuc Khanh Nhi; Tran Phuong Ha; Le Tuan Anh; Ton That Huu Dat; Phung Thi Thuy Oanh; Nguyen Thi Minh Phuong; Vo Thi Kim Thu; Ho Viet Duc; Hoang Le Tuan Anh (Natural Product Research, 2022)

Secondary metabolites from Valeriana jatamansi with their anti-inflammatory activity - Le Huyen Tram; Nguyen Van Thong; Le Thi Thuy; Nguyen Tuan Anh; Nguyen Hoang Minh; Tran Thi Minh; Nguyen Thi Hong Phuong; Tran Thu Ha; Thi Minh Nguyet Nguyen; Duc Dat Le; Nguyen Dinh Hiep; Jong-Tae Park; et al. (Natural Product Research, 2022)

A new triterpenoid from the stems of Kadsura coccinea with antiproliferative activity - Le Huyen Tram; Tran Thu Huong; Le Thi Thuy; Nguyen Van Thong; Nguyen Tuan Anh; Nguyen Hoang Minh; Tran Thu Ha; Dao Anh Dung; Nguyen Phuong Thao; Phuong Thien Thuong; Duc Dat Le; Nguyen Dinh Hiep; et al. (Natural Product Research, 2022)

Cytotoxic activity of steroidal glycosides from the aerial parts of Solanum torvum collected in Thua Thien Hue, Vietnam - Le Canh Viet Cuong; Le Thi Lien; Nguyen Thi Minh Phuong; Vo Thi Kim Thu; Tran Phuong Ha; Ton That Huu Dat; Pham Thi Hai Ha; Tran Thi Phuong Anh; Hoang Le Tuan Anh (Natural Product Research, 2021)

Zoning Seagrass Protection in Lap An Lagoon, Vietnam Using a Novel Integrated Framework for Sustainable Coastal Management - Nam Thang Ha; Tien Dat Pham; Thi Thuy Hang Tran (Wetlands, 2021)

Learning from multimodal and multisensor earth observation dataset for improving estimates of mangrove soil organic carbon in Vietnam - Nga Nhu Le; Tien Dat Pham; Naoto Yokoya; Nam Thang Ha; Thi Thu Trang Nguyen; Thi Dang Thuy Tran; Tien Duc Pham (International Journal of Remote Sensing, 2021)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

Unsubstituted and Methylated PAHs in Surface Sediment of Urban Rivers in the Red River Delta (Hanoi, Vietnam): Concentrations, Profiles, Sources, and Ecological Risk Assessment - Anh Quoc Hoang; Shin Takahashi; Nhu Da Le; Thi Thu Ha Hoang; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen; Thi Xuan Binh Phung; Thi Anh Huong Nguyen; Huu Tuyen Le; Minh Tue Nguyen; Minh Binh Tu; et al. (Bulletin of Environmental Contamination and Toxicology, 2021)

Plant-derived bioactive compounds produced by Streptomyces variabilis LCP18 associated with Litsea cubeba (Lour.) Pers as potential target to combat human pathogenic bacteria and human cancer cell lines - Ngoc Tung Quach; Quang Huy Nguyen; Thi Hanh Nguyen Vu; Thi Thu Hang Le; Thi Thu Thuy Ta; Tien Dat Nguyen; Thuoc Van Doan; The Van Nguyen; Tat Thanh Dang; Xuan Canh Nguyen; Hoang Ha Chu; Quyet Tien Phi (Brazilian Journal of Microbiology, 2021)

The use of radar and optical satellite imagery combined with advanced machine learning and metaheuristic optimization techniques to detect and quantify above ground biomass of intertidal seagrass in a New Zealand estuary - Nam Thang Ha; Merilyn Manley-Harris; Tien Dat Pham; Ian Hawes (International Journal of Remote Sensing, 2021)

Stercufoetin A, new oleanane-type triterpenoid from the leaves of Sterculia foetida L. - Nguyen Kim Tuyen Pham; Trung Duan Nguyen; Tran Duy Cuong Doan; Tuan Dat Ha; Nguyen Minh An Tran; Trong Duc Tran; Dinh Tri Mai; Tan Phat Nguyen (Natural Product Research, 2021)

Icariin reduces bone loss in a Rankl‐induced transgenic medaka ( Oryzias latipes ) model for osteoporosis - Cuong V. Pham; Thanh T. Pham; Thuy T. Lai; Dat C. Trinh; Huong V. M. Nguyen; Tam T. M. Ha; Thuong T. Phuong; Long D. Tran; Christoph Winkler; Thuy T. To (Journal of Fish Biology, 2021)
Given the limitations and side effects of many synthetic drugs, natural products are an important alternative source for drugs and medications for many diseases. Icariin (ICA), one of the main flavonoids from plants of the Epimedium genus, has been shown to ameliorate osteoporosis and improve bone health in preclinical studies. Those studies have used different in vivo models, mostly rodents, but the underlying mechanisms remain unclear. The present study shows, for the first time, that ICA reduces bone damage in a Rankl‐induced medaka fish ( Oryzias latipes ), a non‐rodent osteoporosis model. Live imaging was previously performed in this model to characterize antiresorptive and bone‐anabolic properties of drugs. Here, a new quantification method (I M ) was established based on the length of mineralized neural arches to quantify levels of bone mineralization damage and protection in early post‐embryonic fish. This method was validated by quantification of three levels of bone damage in three independent Rankl fish lines, and by the determination of different degrees of severity of osteoporosis‐like phenotypes in one Rankl line exposed to variable Rankl induction schemes. I M was also used to quantify the efficacy of alendronate and etidronate, two common anti‐osteoporotic bisphosphonates, and revealed comparable bone protective effects for ICA and alendronate in this fish osteoporosis model. This study's data support the value of the medaka fish model for bone research and establish a method to screen for novel osteoprotective compounds.

In vitro study on α-amylase and α-glucosidase inhibitory activities of a new stigmastane-type steroid saponin from the leaves of Vernonia amygdalina - Hoang Le Tuan Anh; Le Ba Vinh; Le Thi Lien; Pham Viet Cuong; Masayoshi Arai; Tran Phuong Ha; Hoang Ngoc Lin; Ton That Huu Dat; Le Canh Viet Cuong; Young Ho Kim (Natural Product Research, 2021)

Antibiotic and antiparasitic residues in surface water of urban rivers in the Red River Delta (Hanoi, Vietnam): concentrations, profiles, source estimation, and risk assessment - Nhu Da Le; Anh Quoc Hoang; Thi Thu Ha Hoang; Thi Anh Huong Nguyen; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen; Van Chung Hoang; Thi Xuan Binh Phung; Huu Tuyen Le; Cao Son Tran; Thu Hien Dang; et al. (Environmental Science and Pollution Research, 2021)

Anti-inflammatory constituents from Psychotria prainii H. Lév - Phi Hung Tran; Viet Dung Le; Thi Ha Do; Thi Luyen Nguyen; Phuong Thao Nguyen; Trong Thong Nguyen; Tien Dat Nguyen (Natural Product Research, 2019)

Antimicrobial and Cytotoxic Properties of Bioactive Metabolites Produced by Streptomyces cavourensis YBQ59 Isolated from Cinnamomum cassia Prels in Yen Bai Province of Vietnam - Hanh-Nguyen Thi Vu; Dat Tien Nguyen; Huy Quang Nguyen; Ha Hoang Chu; Son Ky Chu; Minh Van Chau; Quyet-Tien Phi (Current Microbiology, 2018)

A new anti-inflammatory β-carboline alkaloid from the hairy-root cultures of Eurycoma longifolia - Pham Bich Ngoc; Thanh Binh Pham; Hai Dang Nguyen; Thu Trang Tran; Hoang Ha Chu; Van Minh Chau; Jeong-Hyung Lee; Tien Dat Nguyen (Natural Product Research, 2016)

Toxicity and anticancer effects of an extract from Selaginella tamariscina on a mice model - Le Minh Ha; Do Thi Thao; Hoang Thanh Huong; Chau Van Minh; Nguyen Tien Dat (Natural Product Research, 2012)

Inhibitory effects on nuclear factor κB of the Vietnamese freshwater cyanobacteria - Tien Dat Nguyen; Thi Thuy Duong; Thi Phuong Quynh Le; Van Minh Chau; Minh Ha Le; Dinh Kim Dang; Jung Joon Lee; Marie-Lise Bourguet-Kondracki (Medicinal Chemistry Research, 2011)